The Jurisdiction of Judicial Police in Investigating Crimes of Spreading Rumors and Fake News in the UAE Legislation : A Comparative Study - Al-Mesafri, Rashid; Al-Wasmi, Mona (Journal of Legal Sciences, 2026)
This research aims to study the jurisdiction of the judicial police to search and investigate the crimes of spreading rumors and false news in the UAE legislation. Rumors and false news are emerging phenomena on social media and digital media, and pose a major challenge to societies, including the UAE. The research included a comparative and comparative analysis of the relevant UAE legislation that regulates the spread of rumors and false news. The criminal provisions and legal procedures followed by the judicial police to combat these crimes were highlighted. The relevant legal texts and UAE legislation were analyzed, with a focus on the powers, duties and mechanisms available to the judicial police. To investigate crimes of spreading rumors and false news. The research relied on the analytical descriptive approach, as well as the comparative approach for analyzing legal texts, judicial sources, and relevant legal literature. Data was collected from multiple sources such as laws, legislation, judicial decisions, and previous studies. This research has reached results that contribute to providing a deeper understanding of the jurisdiction of the judicial police in the field of combating the crimes of spreading rumors and false news in the UAE legislation. The results and recommendations resulting from this study may provide a basis for developing and improving legal policies and procedures related to combating these crimes in the Emirates and other countries.